Mould sticking, fouling and cleaning - Packham, D. E. (David Ernest), 1939- (Rapra review reports., 2002)
A large number of objects produced from polymers are moulded. One of the main problems of moulding with polymers is the fact that the articles produced often stick in the mould. An associated problem is that of mould fouling where deposits from previous items stick to the surface of the mould and these in turn cause blemishes on the next product. Mould release and mould fouling have serious implications to the polymer industry in terms of limiting the production rate and in an industry where 'time is money' this can represent a significant cost to that industry. This review first discusses mou.